Genetic Basis of Aerobically Supported Voluntary Exercise: Results from a Selection Experiment with House Mice. Issue 3 (1st November 2020) - Hillis, David A; Yadgary, Liran; Weinstock, George M; Pardo-Manuel de Villena, Fernando; Pomp, Daniel; Fowler, Alexandra S; Xu, Shizhong; Chan, Frank; Garland, Theodore
Abstract: House mice from 4 replicate lines selectively bred for 61 generations for voluntary wheel-running behavior were compared with 4 non-selected control lines using multiple genome-wide analytical techniques on both haplotype and single nucleotide polymorphism data...... Abstract: The biological basis of exercise behavior is increasingly relevant for maintaining healthy lifestyles. Various quantitative genetic studies and selection experiments have conclusively demonstrated substantial heritability for exercise behavior in both humans and laboratory rodents. In the "High Runner" selection experiment, four replicate lines of Mus domesticus were bred for high voluntary wheel running (HR), along with four nonselected control (C) lines. After 61 generations, the genomes of 79 mice (9–10 from each line) were fully sequenced and single nucleotide polymorphisms (SNPs) were identified. We used nested ANOVA with MIVQUE estimation and other approaches to compare allele frequencies between the HR and C lines for both SNPs and haplotypes. Approximately 61 genomic regions, across all somatic chromosomes, showed evidence of differentiation; 12 of these regions were differentiated by all methods of analysis. Gene function was inferred largely using Panther gene ontology terms and KO phenotypes associated with genes of interest. Some of the differentiated genes are known to be associated with behavior/motivational systems and/or athletic ability, including Sorl1, Dach1, and Cdh10 . Sorl1 is a sorting protein associated with cholinergic neuron morphology, vascular wound healing, and metabolism. Dach1 is associated with limb bud development and neural differentiation. Cdh10 is a calcium ion binding protein associated with phrenic neurons. Overall, these results indicate that selective breeding for high voluntary exercise has resulted in changes in allele frequencies for multiple genes associated with both motivation and ability for endurance exercise, providing candidate genes that may explain phenotypic changes observed in previous studies.